Vitamin D status in early childhood is not associated with cognitive development and linear growth at 6-9 years of age in North Indian children: a cohort study. - Chowdhury, Ranadip; Taneja, Sunita; Kvestad, Ingrid; Hysing, Mari; Bhandari, Nita; Strand, Tor A. (Nutrition Journal, 2020)
Background: Vitamin D is important for brain function and linear growth. Vitamin D deficiency during pregnancy has been linked with impaired neurodevelopment during early childhood. However, there is limited evidence from population-based studies on the long-term impact of vitamin D deficiency on cognitive development and linear growth. The objective of the current analysis is to examine whether vitamin D deficiency during infancy and early childhood is associated with cognitive development and linear growth measured in school age.Methods: This is a follow-up study of a placebo-controlled trial among 1000 North Indian children 6-30 months of age. We measured growth and neurodevelopment in 791 of these children when they were 6-9 years old. Neurodevelopment was measured using the Wechsler Intelligence Scale for Children, 4th edition INDIA, the Crichton Verbal Scale, NEPSY-II subtests, and the BRIEF 2. We categorized vitamin D concentrations during infancy and early childhood according to the US Institute of Medicine's recommendations; serum 25(OH)D < 12 ng/ml as deficient; 12-20 ng/ml as inadequate; > 20 ng/ml as sufficient. In multivariable regression models, adjusting for relevant confounders, we estimated the association between vitamin D status, growth and neurodevelopmental outcomes.Results: Among the 791 children, baseline vitamin D status was available for 716. Of these, 45.8% were vitamin D deficient, 32.7% were inadequate, and 21.5% were sufficient. Vitamin D status was not associated with any of the cognitive outcomes or linear growth [Adjusted β coefficient for height for age z-score between deficient and sufficient children was - 0.06 (95% CI - 0.24 to 0.11)] at follow up.Conclusion: Our findings do not support the notion that poor vitamin D status in early childhood is an important limitation for cognitive development and linear growth.Trial Registration: The trial was first registered at www.clinicaltrials.gov as NCT00717730 in July, 2008, and at CTRI/2010/091/001090 in August, 2010 and then as CTRI/2016/11/007494 in November 2016.